Analysis of Physical Activity Levels, Economic Status and Depression in People with Diabetes Mellitus in Bandung City - Kirey, Anastasya Putri; Kusnaedi, Kusnaedi; Hidayat, Yusuf; Muda, Iskandar; Wijaya, Muhamad Suma; Yulianto, Ari Gana; Sofyan, Davi (Indonesian Journal of Sport Management, 2024)
Insufficient physical activity can be at risk of causing other additional diseases in people with diabetes mellitus, one of which is depression. Apart from that, there is also a lot of evidence showing a relationship between socio-economic status (SES) and the prevalence of diabetes. The aim of this research is to find out how much and how the level of physical activity, economic status and depression are related to people with diabetes mellitus in the city of Bandung. The research method used was quantitative descriptive, with Chi-Square test correlation data analysis, totaling 166 subjects. The results of this study show that the level of physical activity in people with diabetes mellitus in Bandung City tends to be moderate, with low economic status and normal levels of depression. Based on the results of data analysis using the Chi-square test, the significance value between physical activity and economic status was 0.272 (P>0.05), meaning that there was no significant relationship. Between physical activity and depression, a significance value of 0.273 (P>0.05) was obtained, meaning that there was no significant relationship. Economic status and depression obtained a significance value of 0.085 (P>0.05), meaning that there is no significant relationship between economic status and depression in people with diabetes mellitus in Bandung City. The conclusion of this research is that in people with diabetes mellitus in the city of Bandung who participated in the chronic diabetes service program, there was no significant relationship between physical activity, economic status and depression, because the sufferers were active in carrying out activities that could help cure them